O sentido da viagem na escritura das Galáxias: o espaço em palimpsesto e a escrita da tradição poética - Silva, Viviani Bernardes da (2008)
Galáxias (1984), Haroldo de Campos prepares a record critic of the poetic tradition in providing epifanias, to raise their cosmos space in the sensitivity of the reader, and the intent of the subject-writer. From its conception as a livro-mar, open to travel by the most different genres and poetic spaces emerge a proposal for research around the writing and space.The galactic space breaks with the design of a study of literature diachronic. In this area, the different styles of composition stage poetic, while the prospect of becoming one of poetic creation. The utopia of a universal language is satiates in building a metaphor palpable, experiencing a written calligraphic, influenced by how empty the Zen Buddhist cult to create a language suspended.The trip is proposed by writing this reading of galactic space, based on the design of deed of Roland Barthes. The methodology of reflection on the galactic space includes a discussion of the literary genres and the book-trip. Besides it talk about the difference between the text and writing in this space and the significance of the journey by the text. From these thoughts and notes on the area of Haroldo s Galáxias, it was possible to see that this space is understood as a spirally structure. The subject writer-critic proposes to write the protection of a cross poetic tradition. The dream of writing the incommunicado differentiates this from the genre of travel literature and travel